Prevalence and characteristics of migraine in women of reproductive age in Istanbul, Turkey: A population based survey - (:unkn) unknown (TOHOKU UNIV MEDICAL PRESS, 2005)
Migraine is more common in female and onset of migraine is most commonly seen in the second and third decades of life. In this study, we aimed to estimate the prevalence and characteristics of migraine among women of ages between 15 to 45 years in Turkey. This is the first study to target this age group. The women were interviewed on a door-to-door basis, from early morning to late evening. Once responded positively to headache, an in-depth interview was performed questioning for migraine features. Diagnosis was made from a questionnaire by eight neurologists. One thousand eight hundred thirty five (1,835) out of 96,000 women living in Maltepe which is a town of Istanbul participated in this study. The prevalence of migraine in females aged 15-45 (reproductive ages) was 15.8% (95% CI, 0.142-0.176). This study showed that migraine onset Occurred at a mean age of 22.7, 33% having family history, and with migraine with and without aura having near equal frequencies. The prevalence of migraine in women of reproductive ages in Istanbul as found in our study is lower than that reported in United States and Europe countries, but higher than that in Middle and Far Eastern countries. (c) 2005 Tohoku University Medical Press.
Keywords: migraine; women of reproductive ages; prevalence; Turkey; TENSION-TYPE HEADACHE; UNITED-STATES; CLINICAL CHARACTERISTICS; GENERAL-POPULATION; EPIDEMIOLOGY; CARE; JAPAN